Barriers to Faculty Development Program for Medical Education: Experience from Saudi Arabia - Hussein Algahtani; Bader Shirah; Ahmed Aldarmahi; Lana Alshawwa; Ara Tekian; John Norcini (Dr. Sulaiman Al Habib Medical Journal)
Background: Many factors may impede faculty development programs. These barriers can be categorized according to the source of their possible origin: faculty level and institutional level. It is of paramount importance to know these barriers to determine the appropriate ways to solve them so as to make implementing faculty development programs possible. This study aims to identify the barriers to faculty development program in medical education in Saudi Arabia. Methods: This cross-sectional survey was conducted in the Western region of Saudi Arabia. The participants, who hailed from multiple universities, were asked to fill out a predesigned self-administered questionnaire. The survey questionnaire, which was generated from the literature, consists of 54 items. Results: The most important institution-related barrier for a faculty development program was the inadequacy of managerial and organizational support. The most important personal barrier for faculty development program was resistance to change. The most important curriculum-related barrier for a faculty development program was lack of follow-up activities. The most important student and research-related barrier for faculty development program was underprepared students. Conclusion: Our study demonstrated that faculty development in Saudi Arabia is in its infancy with several barriers impeding its implementation and success. This study validated these predetermined barriers in the Saudi context. There is a need to overcome all barriers on both faculty and institutional levels in order to establish an outstanding faculty development program. Institutions have to realize the importance of a faculty development program as two-thirds of the barriers were related to institutions.